The existence of the solutions of the complex mathematical programming problem - Jasilionis, R. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Ю. Ясилионис. О существовании решений сложных задач математическое программированияR. Jasilionis. Sudėtingų matematinio programavimo uždavinių sprendinių egzistencija